Baserer de såkaldte Bartholinannaler sig på danske middelalderlige årbøger? - Clausen, Svend (Fund og Forskning, 2022)
Svend Clausen: Are the Annales Bartholiniani based on Danish medieval annals? The article discusses the so-called Annales Bartholiniani, written by the Danish scholar Thomas Bartholin (1659‑1690). Analysis of a series of events that are clearly dated incorrectly in the Annales Bartholiniani and a comparison of the dating of these events with the content of Danish medieval annals suggest that the inaccurate dating of such events in the Annales Bartholiniani must go back to the Danish medieval annalistic traditions. This proves that a great deal of the content of the Annales Bartholiniani must go back either directly or indirectly to the content of Danish medieval annals. It also points to the fact that there needs to be more discussion of the Annales Bartholiniani in future studies, as they also contain a great deal of information not available elsewhere, and the close link between them and the content of Danish medieval annals makes it much more likely that Bartholin may have used also some Danish medieval annals now lost in addition to the medieval annals still known to us. In this respect, such an identified close link between the Annales Bartholiniani and the known content of the Danish medieval annalistic traditions may help significantly in explaining also some of the otherwise unknown information present in the Annales Bartholiniani. Discussions of the content for years such as 1087 and 1142, for example, suggest that specific details such as these may go back directly or indirectly to a now lost medieval Danish annalistic tradition.